Association between CD56, CD38 and chronic endometritis and analysis of pregnancy prognosis: a single-center retrospective cohort study - Kong, Yanni; Zhou, Shiwei; Zhou, Qianru (Frontiers in Medicine, 2026)
BackgroundThe clinical symptoms of chronic endometritis (CE) are atypical, but it is correlated with adverse pregnancy outcomes. The accuracy of its detection needs to be further improved. This article aims to study the association between immunohistochemical CD56, CD38, and CE, and to explore their effect on pregnancy outcomes.MethodsA retrospective analysis was conducted on the clinical data of 844 patients who underwent hysteroscopy check/surgery in the Department of Traditional Chinese Medicine of Zhejiang Provincial People’s Hospital from May 1, 2023 to October 31, 2024. The expression levels of CD56 and CD38 and the 12-week continuous pregnancy rate were compared between the CE group and the non-CE group. The optimal cut-off values of CD56 and CD38 were taken based on the ROC curve to explore their diagnosis value for CE and predictive value for pregnancy outcomes.ResultsAmong the 844 patients, the levels of CD56 and CD38 in the CE group were both higher than those in the non-CE group (P < 0.05). Spearman correlation analysis indicated that CD56 and CD138, CD38, and CD138, and CD56 and CD38 were correlated, respectively (r = 0.18, r = 0.38, r = 0.33, P < 0.001 for all). The optimal cut-off value was selected based on the ROC curve. The incidence of chronic endometritis was higher in the high-value CD56 group (≥ 23.5 cells/HPF), and in the high-value CD38 group (≥ 0.5 cells/HPF) (χ2 = 15.994, χ2 = 129.067, and both P < 0.001). However, there were no statistically significant differences in the 12-week continuous pregnancy rates between the CE group and the non-CE group, the high-value CD56 group and the low-value CD56 group, and the high-value CD38 group and the low-value CD38 group (P > 0.05). Taking the pregnancy outcome as the predictive target and re-taking the optimal cutoff value, the 12-week continuous pregnancy rate of the new high-value CD38 group (≥ 9.5 cells/HPF) was lower than that of the new low-value CD38 group (< 9.5 cells/HPF) (χ2 = 5.504, P = 0.019), and the difference was statistically significant.ConclusionCD56 and CD38 are associated with CE. Various immunohistochemicals can be utilized to improve the accuracy of CE diagnosis, and CD38 is better for evaluating pregnancy outcomes.